Inside Cover: 2, 6‐Difluorobenzamide Inhibitors of Bacterial Cell Division Protein FtsZ: Design, Synthesis, and Structure–Activity Relationships (ChemMedChem 16/2017). (22nd August 2017) - Straniero, Valentina; Zanotto, Carlo; Straniero, Letizia; Casiraghi, Andrea; Duga, Stefano; Radaelli, Antonia; De Giuli Morghen, Carlo; Valoti, Ermanno
Abstract : The inside cover picture shows the general chemical structure of a new class of antimicrobial agents. These antibiotics were designed in order to fight the emerging antimicrobial resistance, thanks to their peculiar and bactericidal mechanism of action: the inhibition of the essential bacterial division protein FtsZ. We defined the structure–activity relationship (SAR) of a series of 3‐(benzodioxan‐2‐yl)‐2, 6‐difluorobenzamides, substituted at the 1, 4‐benzodioxane or modified at the benzodioxane scaffold, and we tested them for the activity against strains of methicillin‐sensitive or methicillin‐resistant Staphylococcus aureus (MRSA). More information can be found in the Full Paper by Valentina Straniero, Ermanno Valoti et al. onpage 1303 in Issue 16, 2017 (DOI:10.1002/cmdc.201700201 ).